Aqueous adhesive composition

CN117417133BActive Publication Date: 2026-10-20ROCKWOOL AS
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202311385481.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-10-05
Filing Date
2019-10-07
Publication Date
2026-10-20
Estimated Expiration
2039-10-07

AI Technical Summary

Technical Problem

[0010]然而,这些粘合剂中的许多仍然相对昂贵,因为它们基于相对昂贵的基础材料

Benefits of technology

[0020]本发明人惊奇地发现,可以获得矿棉产品,其包含被粘合剂组合物的固化得到的粘合剂粘结的矿物纤维,由此所述粘合剂组合物可以由廉价的可再生材料大量生产,不包含或仅包含少量的任何腐蚀性和/或有害物质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117417133B_ABST
    Figure CN117417133B_ABST
Patent Text Reader

Abstract

The present invention relates to an aqueous binder composition for mineral fibres.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of application number 201980075614.7. Invention Field

[0002] The present invention relates to an aqueous adhesive composition for mineral fibers, a method for producing bonded mineral fiber products using said adhesive, and a mineral fiber product comprising mineral fibers in contact with a cured adhesive. Background Technology

[0003] Mineral fiber products typically comprise man-made glass fibers (MMVF), such as glass fiber, ceramic fiber, basalt fiber, slag wool, mineral wool, and asbestos, which are bonded together by a cured thermosetting polymer adhesive. For use as thermal or acoustic insulation products, bonded mineral fiber mats are typically prepared by converting a melt made from suitable raw materials into fibers using conventional methods, such as a rotary cup process or a cascade rotor process. The fibers are blown into a forming chamber and then, while still hot in the air, sprayed with an adhesive solution, and then randomly deposited as mats or nets onto a traveling conveyor. The fiber mats are then transferred to a curing oven, where hot air is blown over the mats to cure the adhesive and firmly bond the mineral fibers together.

[0004] In the past, phenolic resins were the preferred adhesive resins, which can be economically produced and can be chain-extended with urea before being used as adhesives. However, existing and proposed regulations aimed at reducing or eliminating formaldehyde release have led to the development of formaldehyde-free adhesives, such as adhesive compositions based on polycarboxylated polymers and polyols or polyamines, as disclosed in EP-A-583086, EP-A-990727, EP-A-1741726, US-A-5,318,990, and US-A-2007 / 0173588.

[0005] Another class of non-phenolic formaldehyde adhesives are products of addition / elimination reactions of aliphatic and / or aromatic anhydrides with alkanolamines, such as those disclosed in WO 99 / 36368, WO 01 / 05725, WO 01 / 96460, WO 02 / 06178, WO 2004 / 007615, and WO2006 / 061249. These adhesive compositions are water-soluble and exhibit excellent adhesive properties in terms of curing speed and cured density. WO 2008 / 023032 discloses this type of urea-modified adhesive, which provides mineral wool products with reduced moisture absorption.

[0006] Because some of the starting materials used to produce these adhesives are rather expensive chemicals, there has always been a need to provide formaldehyde-free adhesives that can be produced economically.

[0007] Another effect associated with previously known aqueous adhesive compositions for mineral fibers is that at least most of the starting materials used to produce these adhesives are derived from fossil fuels. A continuing consumer trend favors products made entirely or at least partially from renewable materials, thus creating a need for mineral wool adhesives made at least partially from renewable materials.

[0008] Another effect associated with previously known aqueous binder compositions for mineral fibers is that they contain corrosive and / or harmful components. This necessitates protective measures for machinery involved in the production of mineral wool products to prevent corrosion, and also requires safety measures for personnel operating such machinery. This leads to increased costs and health problems, thus creating a need for binder compositions for mineral fibers with reduced corrosive and / or harmful material content.

[0009] Meanwhile, many adhesives for mineral fibers have been provided, which are largely based on renewable starting materials. In many cases, these adhesives, which are largely based on renewable resources, are also formaldehyde-free.

[0010] However, many of these adhesives remain relatively expensive because they are based on relatively expensive base materials. Summary of the Invention

[0011] Therefore, the object of the present invention is to provide an adhesive composition particularly suitable for bonding mineral fibers, which uses renewable materials as starting materials, reduces or eliminates corrosive and / or harmful materials, and has a relatively low production cost.

[0012] Another object of the present invention is to provide mineral wool products bonded with such adhesive composition.

[0013] Another object of the present invention is to provide a method for manufacturing such mineral wool products.

[0014] According to a first aspect of the invention, a preferably formaldehyde-free aqueous adhesive composition is provided, comprising:

[0015] - One or more components in the form of oxidized lignin (i);

[0016] - Components in the form of one or more crosslinking agents (ii);

[0017] - One or more components in the form of plasticizers (iii).

[0018] According to a second aspect of the invention, a method for producing a bonded mineral fiber product is provided, comprising the step of contacting the mineral fibers with the above-described aqueous adhesive composition.

[0019] According to a third aspect of the invention, a mineral wool product is provided, comprising mineral fibers in contact with a cured adhesive composition according to the invention.

[0020] The inventors have surprisingly discovered that mineral wool products can be obtained, which contain mineral fibers bonded by an adhesive obtained by curing an adhesive composition, wherein the adhesive composition can be mass-produced from inexpensive renewable materials and contains little or no corrosive and / or harmful substances. Attached Figure Description

[0021] Figure 1 A cross-section of the possible lignin structure is shown.

[0022] Figure 2 The results showed that softwood lignin is mainly composed of coniferyl alcohol units, while hardwood lignin has a higher eugenol content.

[0023] Figure 3 This shows that there are at least four types of industrial lignin on the market.

[0024] Figure 4 This presents a summary of the properties of industrial lignin.

[0025] Figure 5 A schematic diagram of the shear strength test for bonded lap joints is shown.

[0026] Figure 6 The images show sulfate lignin and ammonia-oxidized sulfate lignin (AOL). 31 P NMR.

[0027] Description of preferred implementation scheme

[0028] The aqueous adhesive composition for mineral fibers according to the present invention comprises

[0029] - One or more components in the form of oxidized lignin (i);

[0030] - Components in the form of one or more crosslinking agents (ii);

[0031] - One or more components in the form of plasticizers (iii).

[0032] In a preferred embodiment, the adhesive according to the invention is formaldehyde-free.

[0033] For the purposes of this application, the term "formaldehyde-free" is defined as indicating that the formaldehyde release from the mineral wool product therein is less than 5 μg / m³. 2 / h, preferably below 3μg / m 2 / h mineral wool product. Preferably, testing is performed according to ISO 16000 to test aldehyde release.

[0034] Component (i)

[0035] Component (i) is in the form of one or more oxidized lignins.

[0036] Lignin, cellulose, and hemicellulose are the three main organic compounds in plant cell walls. Lignin can be considered the glue that holds cellulose fibers together. Lignin contains both hydrophilic and hydrophobic groups. It is the second most abundant natural polymer in the world after cellulose, and is estimated to represent 20% to 30% of the total carbon content in biomass, exceeding 1 billion tons globally.

[0037] Figure 1 A cross-section of the possible lignin structure is shown.

[0038] There are at least four types of industrial lignin on the market. These four types are shown in... Figure 3 The fifth possible class, biorefined lignin, is somewhat different because it is described not by the extraction process but by the process of origin, such as biorefining; therefore, it can be similar to or different from any of the other classes mentioned. Each class differs from one another and is suited to different applications. Lignin is a complex, heterogeneous material, and depending on its source, it consists of up to three different phenylpropane monomers. Softwood lignin is primarily composed of coniferyl alcohol units; see [link to relevant documentation]. Figure 2 Therefore, they are more uniform than hardwood lignin, which has a higher eugenol content. See [link to relevant documentation]. Figure 2 The appearance and consistency of lignin vary greatly and are highly dependent on the processing method.

[0039] The properties of these industrial lignins are summarized as follows: Figure 4 As shown.

[0040] Lignin sulfonates from sulfite pulping remain the largest commercial source of lignin, with a capacity of 1.4 million tons. However, aside from these, the sulfate process is currently the most commonly used pulping process and is gradually replacing the sulfite process. It is estimated that global sulfate pulp production generates 78 million tons of lignin annually, but most of it is used for steam and energy combustion. Current kraft paper recycling capacity is estimated at 160,000 tons, but sources indicate that current recycling volume is only 75,000 tons. Sulfate lignin is extracted from black liquor, which is the waste liquid from sulfate or sulfate pulping processes. Currently, three well-known processes are used to produce sulfate lignin: LignoBoost, LignoForce, and SLRP. These three processes are similar because they involve adding CO2 to lower the pH to 9-10, followed by acidification to further lower the pH to approximately 2. The final step involves some combination of washing, leaching, and filtration to remove ash and other contaminants. These three processes are at various stages of commercialization globally.

[0041] The sulfate process introduces thiol groups and stilbene, while also leaving some carbohydrate residues. Since lignin is precipitated from the mother liquor with sulfuric acid, sodium sulfate is also present as an impurity, but this can be avoided by modifying the lignin separation method. The sulfate process results in a high content of phenolic hydroxyl groups; when these groups are ionized (pH above 10), the lignin becomes water-soluble.

[0042] Commercial lignin sulfates are typically of higher purity than lignin sulfonates. Their molecular weight ranges from 1000 to 3000 g / mol.

[0043] Alkali lignin is derived from sodium hydroxide pulping processes primarily used for wheat straw, bagasse, and flax. The properties of alkali lignin are similar to those of sulfate lignin in terms of solubility and total glutaraldehyde (Tg). This process does not use sulfur and there is no covalently bonded sulfur. The ash level is very low. Alkali lignin has low solubility in neutral and acidic media, but is completely soluble in media with pH 12 or higher.

[0044] The lignin sulfonate process introduces a large number of sulfonate groups, making lignin soluble in both water and acidic aqueous solutions. Lignosulfonates contain up to 8% sulfur as sulfonates, while sulfate lignin contains 1-2% sulfur, mostly bonded to lignin. The molecular weight of lignin sulfonates ranges from 15,000 to 50,000 g / mol. Compared to other types of lignin, this lignin contains more residual carbohydrates and has a higher average molecular weight. The typical hydrophobic core of lignin, along with the large number of ionized sulfonate groups, makes this lignin attractive as a surfactant and it is frequently used in applications such as dispersing cement.

[0045] Another type of lignin available is produced through biorefining processes, in which carbohydrates are separated from lignin through chemical or biochemical processes to produce a carbohydrate-rich fraction. The remaining lignin is called biorefined lignin. Biorefining aims to produce energy and alternatives to products derived from fossil fuels and petrochemicals, as well as lignin. Lignin from this process is generally considered a low-value product, or even waste primarily intended for thermal combustion, use as low-grade animal feed, or otherwise disposed of.

[0046] The availability of organic solvent lignin is still being considered at the pilot-scale level. This process involves extracting lignin using water with various organic solvents (most commonly ethanol) and some organic acids. The advantage of this process is the higher purity of the lignin obtained, but it is more expensive compared to other industrial lignins and has solubility in organic solvents rather than water.

[0047] Previous attempts to use lignin as a base compound in adhesive compositions for mineral fibers failed because it proved difficult to find a suitable crosslinking agent that could achieve the desired mechanical properties of cured mineral wool products while simultaneously avoiding harmful and / or corrosive components. Currently, lignin is used as a substitute for petroleum-derived chemicals in adhesive applications or asphalt, such as phenol in phenolic resins. It is also used as an additive in cement and concrete, and in some respects as a dispersant.

[0048] Crosslinking of polymers is generally intended to provide improved properties, such as resistance to mechanical, chemical, and thermal stresses. Lignin is particularly rich in phenolic and aliphatic hydroxyl groups that can react to form crosslinked structures. Different lignins will also possess other potentially available functional groups. The presence of these other groups depends largely on the source-dependent separation of lignin from cellulose and hemicellulose (thiols in sulfate lignin, sulfonates in lignin sulfonates, etc.).

[0049] The crosslinking potential of hydroxyl groups is relatively limited. Lignin is certainly highly reactive to isocyanates and can be used to generate polyurethanes. However, polyurethanes are of little interest due to the toxicity of isocyanates. Similarly, phenolic hydroxyl groups can react with epoxides in a ring-opening manner and participate in standard epoxy / amine curing, but epoxides are also of little interest due to their toxicity. Phenolic hydroxyl groups can activate aromatic rings to react in standard phenolic resins using aldehydes as crosslinking agents, but this is also of little interest due to the toxicity of aldehydes. For example, it is well known to crosslink lignin with aldehydes; see EP3299421A1, which discloses an adhesive containing lignin, glutaraldehyde, ammonia, glucose, and lysine. Several examples of lignin adhesives containing formaldehyde are also known, such as WO14080033 and US3227667.

[0050] The inventors have surprisingly discovered that by using oxidized lignin, it is possible to prepare an adhesive composition for mineral fibers that enables mineral fiber products produced therefrom to have excellent properties, while simultaneously eliminating the need to include harmful and / or corrosive components in the adhesive composition.

[0051] In one embodiment, component (i) is in the form of one or more oxidized sulfate lignins.

[0052] In one embodiment, component (i) is in the form of one or more alkali-oxidized lignins.

[0053] In one embodiment, component (i) is in the form of one or more ammonia-oxidized lignins. For the purposes of this invention, the term "ammonia-oxidized lignin" should be understood as lignin that has been oxidized by an oxidizing agent in the presence of ammonia. The term "ammonia-oxidized lignin" is abbreviated as AOL.

[0054] In an alternative implementation, ammonia is partially or completely replaced by alkali metal hydroxides, particularly sodium hydroxide and / or potassium hydroxide.

[0055] Hydrogen peroxide is a typical oxidizing agent used in the preparation of oxidized lignin.

[0056] In one embodiment, ammonia-oxidized lignin comprises one or more compounds selected from ammonia, amines, hydroxides, or any salts thereof.

[0057] In one embodiment, based on the dry weight of component (i), the content of carboxylic acid groups in component (i) is 0.05 to 10 mmol / g, for example 0.1 to 5 mmol / g, for example 0.20 to 1.5 mmol / g, for example 0.40 to 1.2 mmol / g, for example 0.45 to 1.0 mmol / g.

[0058] In one embodiment, the average carboxylic acid group content of component (i) is greater than 1.5 groups, for example greater than 2 groups, for example greater than 2.5 groups, per component (i) macromolecule.

[0059] Without being bound by any particular theory, the inventors believe that the content of carboxylic acid groups in oxidized lignin plays a significant role in the surprising advantages of the aqueous binder compositions for mineral fibers according to the present invention. In particular, the inventors believe that the carboxylic acid groups in oxidized lignin improve crosslinking properties, and thus give the cured mineral fiber products better mechanical properties.

[0060] Component (ii)

[0061] Component (ii) is in the form of one or more crosslinking agents.

[0062] In one embodiment, component (ii) is one or more crosslinking agents selected from β-hydroxyalkylamides and / or Crosslinking agent forms of zopyridine crosslinking agents.

[0063] β-Hydroxyalkylamide crosslinking agents are curing agents used for acid-functionalized macromolecules. They provide a rigid, durable, corrosion-resistant, and solvent-resistant crosslinked polymer network. It is believed that β-hydroxyalkylamide crosslinking agents cure via esterification to form multiple ester bonds. For optimal curing, the hydroxyl functionality of the β-hydroxyalkylamide crosslinking agent should have an average of at least 2, preferably greater than 2, and more preferably 2-4.

[0064] contain Azoline-based crosslinking agents contain one or more crosslinkers per molecule. Polymers with zoline groups, and typically, contain... Cross-linking agents of zoline can make Azoline derivatives are readily obtained through polymerization. This method is disclosed in patent US6818699 B2.

[0065] In one embodiment, component (ii) is one or more crosslinking agents selected from polyfunctional organic amines, such as alkanolamines, diamines, such as hexamethyldiamine, and triamines.

[0066] In one embodiment, component (ii) is an epoxidized oil based on fatty acid triglycerides.

[0067] It should be noted that epoxidized oils based on fatty acid triglycerides are not considered harmful, and therefore the use of these compounds in the adhesive compositions according to the invention does not render these compositions unsafe to handle.

[0068] In one embodiment, component (ii) is a molecule having three or more epoxy groups.

[0069] In one embodiment, component (ii) is one or more flexible oligomers or polymers, such as low-Tg acrylic acid-based polymers, low-Tg vinyl polymers, or low-Tg polyethers, containing reactive functional groups, such as carbodiimide groups, or anhydride groups, for example... Azoline groups, such as amino groups, or epoxy groups.

[0070] In one embodiment, component (ii) is selected from crosslinking agents that participate in the curing reaction, such as hydroxyalkylamides, alkanolamines, and reaction products of alkanolamines with polycarboxylic acids. Reaction products of alkanolamines with polycarboxylic acids can be found in US6706853B1.

[0071] Not wishing to be bound by any particular theory, the inventors believe that the highly advantageous properties of the aqueous adhesive composition according to the invention are due to the interaction between the oxidized lignin used as component (i) and the aforementioned crosslinking agent. It is believed that the presence of carboxylic acid groups in the oxidized lignin enables it to crosslink very effectively. Another advantageous effect is that the β-hydroxyalkylamide crosslinking agent, preferably used as the crosslinking agent in the aqueous adhesive composition according to the invention, and... The zopyrrolidone crosslinking agents are harmless, particularly non-toxic and non-corrosive. These crosslinking agents interact very effectively with oxidized lignin containing increased amounts of carboxylic acid groups, thereby giving the mineral fiber products according to the invention advantageous mechanical properties.

[0072] In one embodiment, based on the dry weight of component (i), the adhesive composition according to the invention contains component (ii) in an amount of 1 to 40% by weight, for example 4 to 20% by weight, for example 6 to 12% by weight.

[0073] Component (iii)

[0074] Component (iii) is in the form of one or more plasticizers.

[0075] Surprisingly, it has been found that the inclusion of plasticizers in the aqueous adhesive compositions according to the invention strongly improves the mechanical properties of the mineral fiber products according to the invention.

[0076] The term plasticizer refers to a substance added to a material to make it softer, more flexible (by lowering the glass transition temperature Tg) and easier to process.

[0077] In one embodiment, component (iii) is in the form of one or more plasticizers selected from polyethylene glycol, polyethylene glycol ethers, polyethers, hydrogenated sugars, phthalates and / or acids, such as adipic acid, vanillic acid, lactic acid and / or ferulic acid, acrylic polymers, polyvinyl alcohol, polyurethane dispersions, ethylene carbonate, propylene carbonate, lactones, lactams, lactides, acrylic-based polymers having free carboxyl groups and / or polyurethane dispersions having free carboxyl groups.

[0078] In one embodiment, component (iii) is in the form of one or more plasticizers selected from carbonates, such as ethylene carbonate, propylene carbonate, lactones, lactams, lactides, compounds having a lignin-like structure, such as vanillin, acetylsalicylic acid, and solvents used as coalescing agents, such as alcohol ethers, polyvinyl alcohol.

[0079] In one embodiment, component (iii) is in the form of one or more non-reactive plasticizers selected from polyethylene glycol, polyethylene glycol ethers, polyethers, hydrogenated sugars, phthalates and / or other esters, and solvents used as coalescing agents, such as alcohol ethers, acrylic polymers, and polyvinyl alcohol.

[0080] In one embodiment, component (iii) is one or more reactive plasticizers selected from carbonates, such as ethylene carbonate, propylene carbonate, lactones, lactams, lactides, di- or tricarboxylic acids, such as adipic acid or lactic acid, and / or vanillic acid and / or ferulic acid, polyurethane dispersions, acrylic acid-based polymers having free carboxyl groups, and lignin-like compounds, such as vanillin and acetylsuccine.

[0081] In one embodiment, component (iii) is in the form of one or more plasticizers selected from polyethylene glycol and polyethylene glycol ether.

[0082] Another particularly surprising aspect of the invention is that the use of plasticizers with boiling points above 100°C, particularly 140 to 250°C, such as polyethylene glycol and polyethylene glycol ethers, strongly improves the mechanical properties of the mineral fiber products according to the invention, although these plasticizers may at least partially evaporate during the curing of the aqueous adhesives in contact with the mineral fibers, depending on their boiling points.

[0083] In one embodiment, component (iii) is in the form of one or more plasticizers having a boiling point above 100°C, for example 110 to 280°C, more preferably 120 to 260°C, and even more preferably 140 to 250°C.

[0084] Not wishing to be bound by any particular theory, the inventors believe that the effectiveness of these plasticizers in the aqueous adhesive compositions according to the invention is related to their effect of increasing the migration rate of oxidized lignin during the curing process, during which they also evaporate. It is believed that the increased migration rate of lignin or oxidized lignin during curing promotes effective crosslinking. Another advantage in this respect is that plasticizers are virtually absent in the cured mineral fiber products, thus eliminating side effects such as changes in water absorption or mechanical properties with aging.

[0085] In one embodiment, component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 150 to 50,000 g / mol, particularly 150 to 4,000 g / mol, more particularly 150 to 1,000 g / mol, preferably 150 to 500 g / mol, and more preferably 200 to 400 g / mol.

[0086] In one embodiment, component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 4,000 to 25,000 g / mol, particularly 4,000 to 15,000 g / mol, and more particularly 8,000 to 12,000 g / mol.

[0087] In one embodiment, component (iii) is capable of forming covalent bonds with components (i) and / or (ii) during the curing process. Such a component will not evaporate and will remain as part of the composition, but will be effectively modified to avoid introducing undesirable side effects, such as water absorption in the cured product. Non-limiting examples of such components are caprolactone and acrylic-based polymers having free carboxyl groups.

[0088] In one embodiment, based on the dry weight of component (i), component (iii) is present in an amount of 0.5 to 50% by weight, preferably 2.5 to 25% by weight, more preferably 3 to 15% by weight.

[0089] Aqueous adhesive compositions for mineral fibers, comprising components (i) and (iia).

[0090] In one embodiment, the present invention relates to an aqueous adhesive composition for mineral fibers, comprising:

[0091] - One or more components in the form of oxidized lignin (i);

[0092] - Components in the form of one or more modifiers (iia).

[0093] The inventors have discovered that excellent adhesive properties can also be achieved through a two-component system comprising one or more components in the form of oxidized lignin (i) and one or more components in the form of modifiers (iia), as well as any other components optionally mentioned in the context.

[0094] In a preferred embodiment, component (iia) is a modifier in the form of one or more compounds selected from epoxidized oils based on fatty acid triglycerides.

[0095] In one embodiment, component (iia) is a modifier in the form of one or more compounds selected from molecules having three or more epoxy groups.

[0096] In one embodiment, component (iia) is a modifier in the form of one or more flexible oligomers or polymers, such as low-Tg acrylic acid-based polymers, low-Tg vinyl polymers, or low-Tg polyethers, which contain reactive functional groups, such as carbodiimide groups, acid anhydride groups, etc. Azoline groups, such as amino groups, or epoxy groups.

[0097] Without wishing to be bound by any particular theory, the inventors believe that the superior adhesive properties achieved by the adhesive composition for mineral fibers comprising components (i) and (iia) and optionally other components are at least in part due to the effect of the modifier used as component (iia) acting at least in part as a plasticizer and crosslinking agent.

[0098] In one embodiment, based on the dry weight of component (i), the aqueous adhesive composition contains component (iia) in an amount of 1 to 40% by weight, for example 4 to 20% by weight, for example 6 to 12% by weight.

[0099] Other components

[0100] In some embodiments, the aqueous adhesive composition according to the invention comprises other components.

[0101] In one embodiment, the aqueous adhesive composition according to the invention comprises a catalyst selected from inorganic acids, such as sulfuric acid, aminosulfonic acid, nitric acid, boric acid, hypophosphoric acid and / or phosphoric acid, and / or any salt thereof, such as sodium hypophosphite, and / or ammonium salts, such as ammonium salts of sulfuric acid, aminosulfonic acid, nitric acid, boric acid, hypophosphoric acid and / or phosphoric acid. The presence of such a catalyst can improve the curing properties of the aqueous adhesive composition according to the invention.

[0102] In one embodiment, the aqueous binder composition according to the invention comprises a catalyst selected from Lewis acids, which can accept electron pairs from a donor compound to form a Lewis adduct, such as ZnCl2, Mg(ClO4)2, Sn[N(SO2-n-C8F]2, etc. 17 )2]4.

[0103] In one embodiment, the aqueous adhesive composition according to the invention comprises a catalyst selected from metal chlorides, such as KCl, MgCl2, ZnCl2, FeCl3, and SnCl2.

[0104] In one embodiment, the aqueous binder composition according to the invention comprises a catalyst selected from organometallic compounds, such as titanate-based catalysts and tin-based catalysts.

[0105] In one embodiment, the aqueous adhesive composition according to the invention comprises a catalyst selected from chelating agents, such as transition metals, such as iron ions, chromium ions, manganese ions, and copper ions.

[0106] In one embodiment, the aqueous adhesive composition according to the invention further comprises one or more other components in the form of silanes (iv).

[0107] In one embodiment, the aqueous adhesive composition according to the invention comprises one or more coupling agents, such as other components in the form of organofunctional silanes (iv).

[0108] In one embodiment, component (iv) is selected from organofunctional silanes, such as primary or secondary amino-functionalized silanes, epoxy-functionalized silanes, such as polymeric or oligomeric epoxy-functionalized silanes, methacrylate-functionalized silanes, alkyl and aryl-functionalized silanes, urea-functionalized silanes, or vinyl-functionalized silanes.

[0109] In one embodiment, the aqueous adhesive composition according to the invention further comprises one or more components (v) selected from ammonia, amines, or any salt thereof.

[0110] The inventors have discovered that when oxidized lignin is used in component (i), it is particularly useful to include ammonia, amines or any salts thereof as other components, wherein the oxidized lignin is not oxidized in the presence of ammonia.

[0111] In one embodiment, the aqueous adhesive composition according to the invention further comprises other components in the form of urea, particularly in amounts of 5 to 40% by weight, for example 10 to 30% by weight, and 15 to 25% by weight, based on the dry weight of component (i).

[0112] In one embodiment, the aqueous adhesive composition according to the invention further comprises one or more other components in the form of carbohydrates selected from sucrose, reducing sugars, particularly dextrose, polycarbohydrates and mixtures thereof, preferably dextrin and maltodextrin, more preferably glucose syrup, and more preferably glucose syrup with a dextrose equivalent value of DE = 30 to less than 100, for example DE = 60 to less than 100, for example DE = 60-99, for example DE = 85-99, for example glucose syrup with DE = 95-99.

[0113] In one embodiment, the aqueous adhesive composition according to the invention further comprises one or more other components in the form of carbohydrates selected from sucrose and reducing sugars, in an amount of 5 to 50% by weight, for example 5% by weight to less than 50% by weight, for example 10 to 40% by weight, for example 15 to 30% by weight, based on the dry weight of component (i).

[0114] In the context of this invention, adhesive compositions with a sugar content of 50% by weight or higher based on the total dry weight of the adhesive components are considered sugar-based adhesives. In the context of this invention, adhesive compositions with a sugar content of less than 50% by weight based on the total dry weight of the adhesive components are considered non-sugar-based adhesives.

[0115] In one embodiment, the aqueous adhesive composition according to the invention further comprises other components in the form of one or more surfactants, said surfactants being in the form of nonionic and / or ionic emulsifiers, such as polyoxyethylene (4) lauryl ether, such as soybean lecithin, such as sodium dodecyl sulfate.

[0116] In one embodiment, the aqueous adhesive composition according to the invention comprises

[0117] - One or more components (i) in the form of ammoniated lignin, wherein the content of carboxylic acid groups is 0.05 to 10 mmol / g, for example 0.1 to 5 mmol / g, for example 0.20 to 1.5 mmol / g, for example 0.40 to 1.2 mmol / g, for example 0.45 to 1.0 mmol / g, based on the dry weight of component (i);

[0118] - Component (ii) in the form of one or more crosslinking agents, selected from β-hydroxyalkylamide crosslinking agents and / or Azoline crosslinking agent, and / or one or more crosslinking agents selected from polyfunctional organic amines, such as alkanolamines, diamines, such as hexamethyldiamine, and triamines;

[0119] - One or more components (iii) in the form of polyethylene glycol, having an average molecular weight of 150 to 50,000 g / mol, particularly 150 to 4,000 g / mol, more particularly 150 to 1,000 g / mol, preferably 150 to 500 g / mol, more preferably 150 to 300 g / mol, or one or more polyethylene glycols having an average molecular weight of 4,000 to 25,000 g / mol, particularly 4,000 to 15,000 g / mol, more particularly 8,000 to 12,000 g / mol; wherein preferably, based on the dry weight of component (i), the aqueous adhesive composition comprises 1 to 40% by weight, for example 4 to 20% by weight, 6 to 12% by weight of component (ii), and based on the dry weight of component (i), the presence of (iii) is 0.5 to 50% by weight, preferably 2.5 to 25% by weight, more preferably 3 to 15% by weight.

[0120] In one embodiment, the aqueous adhesive composition according to the invention comprises

[0121] - One or more components (i) in the form of ammoniated lignin, wherein the content of carboxylic acid groups is 0.05 to 10 mmol / g, for example 0.1 to 5 mmol / g, for example 0.20 to 1.5 mmol / g, for example 0.40 to 1.2 mmol / g, for example 0.45 to 1.0 mmol / g, based on the dry weight of component (i);

[0122] - One or more modifiers (iia) selected from epoxidized oils based on fatty acid triglycerides.

[0123] In one embodiment, the aqueous adhesive composition according to the invention comprises

[0124] - One or more components (i) in the form of ammonia-oxidized lignin, wherein the average content of carboxylic acid groups in each component (i) macromolecule is greater than 1.5 groups, for example greater than 2 groups, for example greater than 2.5 groups;

[0125] - One or more crosslinking agents (ii), selected from β-hydroxyalkylamide crosslinking agents and / or Azoline crosslinking agent, and / or one or more crosslinking agents selected from polyfunctional organic amines, such as alkanolamines, diamines, such as hexamethyldiamine, and triamines;

[0126] - One or more components (iii) in the form of polyethylene glycol, having an average molecular weight of 150 to 50,000 g / mol, particularly 150 to 4,000 g / mol, more particularly 150 to 1,000 g / mol, preferably 150 to 500 g / mol, more preferably 150 to 300 g / mol, or one or more polyethylene glycols having an average molecular weight of 4,000 to 25,000 g / mol, particularly 4,000 to 15,000 g / mol, more particularly 8,000 to 12,000 g / mol; wherein preferably, based on the dry weight of component (i), the aqueous adhesive composition comprises 1 to 40% by weight, for example 4 to 20% by weight, 6 to 12% by weight of component (ii), and based on the dry weight of component (i), the presence of (iii) is 0.5 to 50% by weight, preferably 2.5 to 25% by weight, more preferably 3 to 15% by weight.

[0127] In one embodiment, the aqueous adhesive composition according to the invention comprises

[0128] - One or more components (i) in the form of ammonia-oxidized lignin, wherein the average content of carboxylic acid groups in each component (i) macromolecule is greater than 1.5 groups, for example greater than 2 groups, for example greater than 2.5 groups;

[0129] - One or more modifiers (iia) selected from epoxidized oils based on fatty acid triglycerides.

[0130] In one embodiment, the aqueous adhesive composition according to the invention comprises essentially the following:

[0131] - One or more components in the form of oxidized lignin (i);

[0132] - Components in the form of one or more crosslinking agents (ii);

[0133] - One or more components in the form of plasticizers (iii);

[0134] - One or more components in the form of coupling agents (iv), such as organofunctional silanes;

[0135] -Optionally one or more components selected from ammonia, amines or any salt thereof in the form of compounds;

[0136] - Components optionally in the form of urea;

[0137] - Components optionally in the form of more reactive or non-reactive organosilicon;

[0138] -Optional hydrocarbon oil;

[0139] -Optionally one or more surfactants;

[0140] -water.

[0141] In one embodiment, the aqueous adhesive composition according to the invention comprises essentially the following:

[0142] - One or more components in the form of oxidized lignin (i);

[0143] - One or more modifiers (iia) selected from epoxidized oils based on fatty acid triglycerides;

[0144] - One or more components in the form of coupling agents (iv), such as organofunctional silanes;

[0145] -Optionally one or more components selected from ammonia, amines or any salt thereof in the form of compounds;

[0146] - Components optionally in the form of urea;

[0147] - Components optionally in the form of more reactive or non-reactive organosilicon;

[0148] -Optional hydrocarbon oil;

[0149] -Optionally one or more surfactants;

[0150] -water.

[0151] Methods for producing mineral fiber products

[0152] The present invention also provides a method for producing mineral fiber products by bonding mineral fibers with an adhesive composition.

[0153] Therefore, the present invention also relates to a method for producing mineral fiber products, comprising the step of contacting mineral fibers with an adhesive composition, said adhesive composition comprising:

[0154] - One or more components in the form of oxidized lignin (i);

[0155] - Components in the form of one or more crosslinking agents (ii);

[0156] - One or more components in the form of plasticizers (iii).

[0157] Curing

[0158] The mesh is cured through a chemical and / or physical reaction of the adhesive components.

[0159] In one implementation, curing takes place in a curing apparatus.

[0160] In one embodiment, curing is carried out at a temperature of 100 to 300°C, for example 170 to 270°C, for example 180 to 250°C, for example 190 to 230°C.

[0161] In one embodiment, curing is carried out in a conventional curing oven used for mineral wool production, with an operating temperature of 150 to 300°C, for example 170 to 270°C, for example 180 to 250°C, for example 190 to 230°C.

[0162] In one implementation, curing takes 30 seconds to 20 minutes, for example 1 to 15 minutes, or for example 2 to 10 minutes.

[0163] In a typical implementation, curing is carried out at a temperature of 150 to 250°C for 30 seconds to 20 minutes.

[0164] The curing process can begin immediately after the adhesive is applied to the fibers. Curing is defined as a process in which the adhesive composition undergoes physical and / or chemical reactions (in the case of chemical reactions, the molecular weight of the compounds in the adhesive composition typically increases), thereby increasing the viscosity of the adhesive composition, usually until the adhesive composition reaches a solid state.

[0165] In one embodiment, the curing of the adhesive in contact with the mineral fibers is carried out in a hot press.

[0166] The curing of adhesives that come into contact with mineral fibers in a hot press has a particular advantage: it enables the production of high-density products.

[0167] In one embodiment, the curing process includes pressure drying. Pressure can be applied by blowing air or gas through / through a mixture of mineral fibers and adhesives.

[0168] Mineral fiber products according to the present invention

[0169] The present invention also relates to mineral fiber products comprising mineral fibers in contact with the cured adhesive composition as described above, i.e., mineral fibers in contact with the cured adhesive produced by curing the aqueous adhesive composition as described above.

[0170] The mineral fibers used can be any of the following: man-made glass fiber (MMVF), glass fiber, ceramic fiber, basalt fiber, slag fiber, rock fiber, stone fiber, etc. These fibers can exist in the form of wool products, such as asbestos products.

[0171] Suitable fiber-forming methods and subsequent production steps for manufacturing mineral fiber products are those conventional in the art. Typically, the binder is sprayed onto the mineral fibers in the air immediately after the mineral melt fibrillation. Based on dry weight, the aqueous binder composition is typically applied in an amount of 0.1 to 18% by weight, preferably 0.2 to 8% by weight, of the bonded mineral fiber product.

[0172] Sprayed mineral fiber mesh is typically cured in a curing oven by means of a flow of hot air. Hot air can be introduced into the mineral fiber mesh from below, above, or in alternating directions in different areas along the length of the curing oven.

[0173] Typically, curing ovens operate at temperatures ranging from about 150°C to about 300°C, such as 170 to 270°C, 180 to 250°C, or 190 to 230°C. Generally, depending on factors such as product density, the residence time in the curing oven is from 30 seconds to 20 minutes, such as 1 to 15 minutes, or 2 to 10 minutes.

[0174] In a typical embodiment, the mineral fiber product according to the invention is cured at a temperature of 150°C to 250°C for 30 seconds to 20 minutes.

[0175] If desired, mineral wool mesh can undergo a shaping process before curing. The bonded mineral fiber product exiting the curing oven can be cut into desired forms, such as wadding. Thus, the produced mineral fiber products are available in various forms, including woven and nonwoven fabrics, mats, wadding, boards, sheets, plates, strips, rolls, granules, and other shapes, which are used for applications such as thermal or sound insulation, shock absorption, building materials, exterior wall insulation, roofing or floor reinforcement, filtration, and more.

[0176] According to the present invention, composite materials can also be produced by combining bonded mineral fiber products with suitable composite layers or laminates such as metals, glass surface pads and other woven or nonwoven materials.

[0177] The mineral fiber products according to the present invention typically have a strength of 6 to 250 kg / m³. 3 Preferred weight is 20 to 200 kg / m³. 3 The density. Mineral fiber products typically have a loss on ignition (LOI) of 0.3% to 18.0%, preferably 0.5% to 8.0%.

[0178] Although the aqueous adhesive composition according to the invention is particularly useful for bonding mineral fibers, it can also be used equivalently in other typical applications of adhesives and sizing agents, such as as an adhesive for foundry sand, glass fiber film, composite materials, moldings, coatings, and metal adhesives.

[0179] Oxidized lignin that can be used as component (i) in an aqueous adhesive composition for mineral fibers according to the present invention and a method for preparing such oxidized lignin.

[0180] In the following sections, we describe oxidized lignin that can be used as component (i) and its preparation.

[0181] The oxidized lignin that can be used as component (i) of the adhesive of the present invention can be prepared by a method including contacting the following.

[0182] - A component containing one or more lignins (a).

[0183] - A component containing ammonia, one or more amine components and / or any salt thereof (b).

[0184] - A component (c) containing one or more oxidizing agents.

[0185] Component (a)

[0186] Component (a) contains one or more lignins.

[0187] In one embodiment of the method according to the invention, component (a) comprises one or more sulfate lignins, one or more alkali lignins, one or more lignin sulfonate lignins, one or more organic solvent lignins, one or more lignins from a biorefining process of lignocellulose raw materials, or any mixture thereof.

[0188] In one embodiment, component (a) comprises one or more sulfate lignins.

[0189] Component (b)

[0190] In one embodiment of the invention, component (b) comprises ammonia, one or more amine components and / or any salt thereof. Therefore, without wishing to be bound by any particular theory, the inventors believe that replacing the alkali metal hydroxides used in previously known lignin oxidation processes with ammonia, one or more amine components and / or any salt thereof plays an important role in the improved properties of oxidized lignin prepared according to the method of the invention.

[0191] The inventors have surprisingly discovered that lignin oxidized by an oxidizing agent in the presence of ammonia or amine contains a significant amount of nitrogen as part of the oxidized lignin structure. Without wishing to be bound by any particular theory, the inventors believe that the improved fire resistance of oxidized lignin, when used in products containing it in adhesive compositions, is at least in part attributed to the nitrogen content in the structure of the oxidized lignin prepared by the method of this invention.

[0192] In one embodiment, component (b) comprises ammonia and / or any salt thereof.

[0193] Not wishing to be bound by any particular theory, the inventors believe that the improved stability of the derivatized lignin prepared according to the present invention is at least in part due to the fact that ammonia is a volatile compound and therefore evaporates from the final product, or can be easily removed and reused. In contrast, residual amounts of alkali metal hydroxides used in previously known oxidation processes have proven difficult to remove.

[0194] Nevertheless, it may be advantageous in the method according to the invention that, in addition to ammonia, one or more amine components and / or any salt thereof, component (b) also contains relatively small amounts of alkali metal and / or alkaline earth metal hydroxides, such as sodium hydroxide and / or potassium hydroxide.

[0195] In the embodiment described, component (b) comprises alkali metal and / or alkaline earth metal hydroxides, such as sodium hydroxide and / or potassium hydroxide, as components other than ammonia, one or more amine components and / or any salt thereof. The amount of alkali metal and / or alkaline earth metal hydroxides is typically small, based on ammonia, for example, 5 to 70 parts by weight, or for example, 10 to 20 parts by weight of alkali metal and / or alkaline earth metal hydroxides.

[0196] Component (c)

[0197] In the method according to the invention, component (c) comprises one or more oxidizing agents.

[0198] In one embodiment, component (c) comprises one or more forms of hydrogen peroxide, organic or inorganic peroxide, molecular oxygen, ozone, halogenated oxidant, or any mixture thereof.

[0199] In the initial step of oxidation, the active group from the oxidant typically removes a proton from the phenolic group, as this bond has the lowest dissociation energy in lignin. Because lignin has the potential to stabilize free radicals through stable anatomy, there are multiple pathways through which the reaction can be continued (but also terminated), yielding a variety of intermediates and final products. Due to this complexity (and the conditions of choice), the average molecular weight can increase and decrease, and in their experiments, the inventors have typically observed a modest increase in average molecular weight of approximately 30%.

[0200] In one embodiment, component (c) comprises hydrogen peroxide.

[0201] Hydrogen peroxide is perhaps the most commonly used oxidant due to its low cost, high efficiency, and relatively small environmental impact. When using hydrogen peroxide in the absence of a catalyst, alkaline conditions and temperature are important because the following reactions lead to the formation of free radicals:

[0202]

[0203]

[0204] The inventors have discovered that the derivatized lignin prepared according to the method of the present invention contains an increased amount of carboxylic acid groups due to the oxidation process. Not wishing to be bound by any particular theory, the inventors believe that the content of carboxylic acid groups in the oxidized lignin prepared according to the method of the present invention plays an important role in the desirable reactivity properties of the derivatized lignin prepared by the method of the present invention.

[0205] Another advantage of the oxidation process is that oxidized lignin is more hydrophilic. Higher hydrophilicity can enhance solubility in water and promote adhesion to polar substrates such as mineral fibers.

[0206] Other components

[0207] In one embodiment, the method according to the invention comprises other components, particularly component (d) in the form of an oxidation catalyst, such as one or more transition metal catalysts, such as ferric sulfate, or catalysts containing manganese, palladium, selenium, or tungsten.

[0208] This oxidation catalyst can increase the reaction rate, thereby improving the properties of oxidized lignin prepared by the method according to the invention.

[0209] Component mass ratio

[0210] Those skilled in the art will use components (a), (b), and (c) in relative amounts to achieve the required degree of oxidation for lignin.

[0211] In one implementation scheme

[0212] - Component (a) contains one or more lignins,

[0213] - Component (b) contains ammonia,

[0214] - Component (c) contains one or more oxidants in the form of hydrogen peroxide.

[0215] The mass ratio of lignin, ammonia, and hydrogen peroxide is such that, based on the dry weight of lignin, the amount of ammonia is 0.01 to 0.5 parts by weight, for example 0.1 to 0.3 parts by weight, or for example 0.15 to 0.25 parts by weight, and the amount of hydrogen peroxide, based on the dry weight of lignin, is 0.025 to 1.0 parts by weight, for example 0.05 to 0.2 parts by weight, or for example 0.075 to 0.125 parts by weight.

[0216] process

[0217] There are more than one possibility to bring components (a), (b), and (c) into contact to achieve the desired oxidation reaction.

[0218] In one implementation, the method includes the following steps:

[0219] - The step of providing one or more components (a) in the form of an aqueous solution and / or dispersion of lignin, wherein the lignin content of the aqueous solution is 1 to 50% by weight, for example 5 to 25% by weight, for example 15 to 22% by weight, for example 18 to 20% by weight, based on the total weight of the aqueous solution;

[0220] -The pH adjustment step by adding component (b), said component (b) comprising an aqueous solution of ammonia, one or more amine components and / or any salt thereof;

[0221] - An oxidation step by adding a component (c) containing an oxidant.

[0222] In one embodiment, a pH adjustment step is performed such that the pH of the resulting aqueous solution and / or dispersion is ≥9, for example ≥10, for example ≥10.5.

[0223] In one embodiment, a pH adjustment step is performed so that the pH of the resulting aqueous solution and / or dispersion is in the range of 10.5 to 12.

[0224] In one implementation, a pH adjustment step is performed to raise the temperature to ≥25°C, and then the temperature is controlled within the range of 25-50°C, for example, 30-45°C, or 35-40°C.

[0225] In one embodiment, during the oxidation step, the temperature is allowed to rise to ≥35°C, and then controlled within the range of 35-150°C, for example 40-90°C, or 45-80°C.

[0226] In one embodiment, the oxidation step is carried out for a period of 1 second to 48 hours, for example 10 seconds to 36 hours, for example 1 minute to 24 hours, for example 2 to 5 hours.

[0227] reaction products

[0228] The present invention also relates to oxidized lignin prepared by the method according to the present invention.

[0229] The inventors have surprisingly discovered that the oxidized lignin prepared according to the method of the present invention has very desirable reactivity properties, and at the same time shows improved fire resistance and improved long-term stability compared to previously known oxidized lignin when used in products in which they are contained in binder compositions.

[0230] Oxidized lignin also exhibits improved hydrophilicity.

[0231] An important parameter for the reactivity of oxidized lignin prepared by the method according to the present invention is the content of carboxylic acid groups in the oxidized lignin.

[0232] In one embodiment, based on the dry weight of component (a), the oxidized lignin prepared according to the present invention has a carboxylic acid group content of 0.05 to 10 mmol / g, for example 0.1 to 5 mmol / g, for example 0.20 to 1.5 mmol / g, for example 0.40 to 1.2 mmol / g, for example 0.45 to 1.0 mmol / g.

[0233] Another method to describe the carboxylic acid group content is to use the average carboxylic acid group content per lignin macromolecule according to the following formula:

[0234]

[0235] In one embodiment, the average carboxylic acid group content of the oxidized lignin prepared according to the present invention is greater than 1.5 groups, for example greater than 2 groups, for example greater than 2.5 groups, for each component (a) macromolecule.

[0236] The following examples are intended to further illustrate the invention without limiting its scope. Detailed Implementation

[0237] Example

[0238] In the following embodiments, several adhesives falling within the scope of this invention were prepared and compared with adhesives according to the prior art.

[0239] The following properties were determined for the adhesive according to the present invention and the adhesive according to the prior art, respectively:

[0240] Solid content of adhesive components

[0241] Before curing, the content of each component in a given adhesive solution is based on the anhydrous mass of the component.

[0242] Response Loss – Definition

[0243] Reaction loss is defined as the difference between the solid content of the binder component and the solid content of the binder.

[0244] Therefore, the reaction loss is calculated by the following formula:

[0245] Reaction loss = (Adhesive component solids - Adhesive solids) / (Adhesive component solids)

[0246] Sulfate lignin from UPM with LignoBoost TMThe following are provided: UPM BioPiva 100 in powder form; oxidized sulfate lignin based on UPM BioPiva 100 (AOL) supplied by Aarhus University as a dispersion in ammonia and water, 18.3% by weight dry matter with a carboxylic acid group content of 0.80 mmol / g, a number-average molecular weight (Mn) of 2503 g / mol, and a weight-average molecular weight (Mw) of 34503 g / mol; Primid XL552 supplied by EMS-CHEMIE AG; 100% dry matter Epocros WS700 supplied by Nippon Shokubai; 25% dry matter Picassian XL702 supplied by Stahl Polymer; 40% dry matter alkali lignin as Protobind 1000 supplied by Green Value Switzerland in powder form; oxidized alkali lignin (AOL) supplied by Aarhus University as an oxidation of 22% dry matter based on Protobind 1000 from Green Value; and lignin derived from the LignoForce process from West... Fraser, Alberta, US is supplied as dry powder. Oxidized lignin derived from LignoForce from West Fraser, Alberta, US (AOL) is supplied by Aarhus University at 22% dry matter. Silanes (Momentive VS-142 40% active, Momentive A1871 100% active, Momentive A187 100% active and Momentive DP200 100% active) are supplied by Momentive and calculated as 100% for simplicity. PEG (200-400), poly(ethylene glycol) dimethyl ether 250 and 1-phenoxy-2-propanol are supplied by Sigma-Aldrich and are assumed to be anhydrous for simplicity.

[0247] Adhesive solids

[0248] The amount of adhesive after curing is called "adhesive solids".

[0249] Disc-shaped asbestos samples (5 cm in diameter and 1 cm in height) were cut from the asbestos and heat-treated at 580°C for at least 30 minutes to remove all organic matter. The solids content of the adhesive mixture was measured by dispensing a sample (approximately 2 g) of the adhesive mixture onto the heat-treated asbestos discs in a foil container. The foil containers containing the asbestos discs were weighed directly before and after the addition of the adhesive mixture. Two such asbestos discs loaded with the adhesive mixture in foil containers were prepared and then heated at 200°C for 1 hour. After cooling and holding at room temperature for 10 minutes, the samples were weighed, and the average of the two results was calculated as the solids content of the adhesive.

[0250] The adhesive with the desired adhesive solids can then be prepared by diluting it with the required amount of water and a 10% aqueous silane solution (Momentive VS-142).

[0251] Mechanical strength study

[0252] Tablet testing:

[0253] The mechanical strength of the binder was tested in the tablet test. For each binder, six tablets were manufactured from a mixture of the binder and asbestos pellets produced from asbestos spinning. The pellets were particles having the same melt composition as asbestos fibers and were generally considered to be waste products from the spinning process. The pellet size used in the tablet composition was 0.25–0.50 mm.

[0254] A sample of the binder solution containing 15% dry solids (4.0 g) was thoroughly mixed with pellets (20.0 g). The resulting mixture was then transferred to a round aluminum foil container (bottom). top (Height = 1.5cm). Then press the mixture firmly into a suitably sized flat-bottomed glass or plastic beaker to create a smooth tablet surface. Prepare six tablets from each adhesive in this manner. Then cure the resulting tablets at 200°C, 225°C, or 250°C for 1 hour (refer to adhesive A: 200°C for 1 hour). After cooling to room temperature, carefully remove the tablets from the container. Age three of the tablets in a water bath at 80°C for 3 hours.

[0255] After drying for 1-2 days, all tablets were broken in a three-point bending test on a Bent Tram machine (test speed: 10.0 mm / min; fracture level: 50%; nominal strength: 30 N / mm). 2 Support distance: 40mm; Maximum deflection: 20mm; Nominal e-modulus: 10000N / mm 2 To study their mechanical strength. The "bottom" of the tablet (i.e., the...) Place it in the machine with the top side facing up.

[0256] bar test

[0257] The mechanical strength of the adhesive was tested in the strip test. For each adhesive, 16 strips were made from a mixture of the adhesive and asbestos pellets produced from asbestos spinning.

[0258] A sample of the adhesive solution containing 15% dry solids (16.0 g) was thoroughly mixed with pellets (80.0 g). The resulting mixture was then filled into four slots in a heat-resistant silicone form to create strips (4 x 5 slots per form; slot top dimensions: length = 5.6 cm, width = 2.5 cm; slot bottom dimensions: length = 5.3 cm, width = 2.2 cm; slot height = 1.1 cm). The mixture placed in the slots was then pressed with a flat metal strip of appropriate size to produce a smooth strip surface. Sixteen strips were obtained from each adhesive in this manner. The resulting strips were then cured typically at 200°C, but other temperatures could also be used, as described in Tables 1-4 and 1-5. The curing time was 1 hour. After cooling to room temperature, the strips were carefully removed from the container. Five of the strips were aged in a water bath at 80°C for 3 hours.

[0259] After drying for 1-2 days, the aged strips and five unaged strips were subjected to a three-point bending test on a Bent Tram machine (test speed: 10.0 mm / min; fracture level: 50%; nominal strength: 30 N / mm). 2 Support distance: 40mm; Maximum deflection: 20mm; Nominal e-modulus: 10000N / mm 2 To study their mechanical strength, the strips were placed in the machine with the "top surface" (i.e., the side with dimensions of length = 5.6 cm and width = 2.5 cm) facing upwards.

[0260] Fiber strip test

[0261] The mechanical strength of the adhesive is tested in the fiber strip test. For each adhesive, it consists of the adhesive and asbestos fibers (from Lapinus). TM of Sixteen strips were made from a mixture of 1000 (presumably referring to a specific compound or concentration). The purpose of this test was to determine the adhesive strength of the binder before and after aging when used in asbestos composites. The strength was determined by three-point bending, from which the flexural strength was derived.

[0262] As described above, an adhesive solution containing 0.5% binder solids of silane (Momentive variant) and 20% binder solids was obtained. A sample of the adhesive solution (470 g) was mixed with MS600 fiber (1350 g) at 3000 rpm for 4 minutes. The resulting mixture was then transferred to a specially designed mold (250 x 50 x 80 mm (L x W x H), 110.0 g each), and pressed using a pneumatic press at a consolidation pressure of 1.1 MPa. The pressure was maintained for 75 seconds to obtain a thickness of 7-10 mm and a density of 0.85-0.95 g / cm³. 3 The strips are then transferred to an oven rack and cured at 200°C, 225°C, or 250°C for 2 hours (refer to Adhesive A: 200°C for 2 hours), producing 16 strips.

[0263] Eight strips were aged at 120°C, and one strip was aged under overpressure in an autoclave for 15 minutes. The aged samples could be left in the autoclave overnight, or stacked in aluminum trays and placed in a room under ambient conditions. Regardless of the storage method, the samples could be tested the following day or later.

[0264] The mechanical properties of unaged strips (8 pieces) and aged (unaged) strips were quantified by three-point bending according to EN310 (test speed: 5 mm / min, fracture level: 10%, nominal E modulus: 1000 N / mm). 2 Nominal strength: 5 N / mm 2 Support distance: 140mm, maximum deflection: 20mm).

[0265] Bending strength is calculated as follows:

[0266]

[0267] Where M is the maximum bending moment. Where F f is the load [N] applied at the failure point, s is the distance between the support strips [mm]. c is the distance from the center of the sample to the outer fiber. Where t is the sample thickness [mm]. And I is the moment of inertia of the cross-section, which for a rectangular geometry is... Where w and t are the width and thickness of the sample [mm], respectively.

[0268] The result of merging is:

[0269]

[0270] Shear strength test of bonded lap joints:

[0271] The mechanical properties of lignin-based adhesives are quantified using the single lap shear test, a well-known method for comparing the shear strength of adhesives, and ASTM standards exist for a wide variety of substrates to which they are bonded, such as ASTM D1002. Sample preparation involves applying an adhesive sample to the substrate, overlapping it with another designated overlapping area, applying pressure to the overlapping area, and curing the adhesive under specified conditions.

[0272] Place 10 mL of lignin-based binder (20% dry solids) in an open beaker and incubate at room temperature in a fume hood for 2 hours, stirring gently with a glass rod every 20–30 minutes. Apply 5 mg of binder (20% dry solids) to the first slide (75 x 25 x 1 mm), overlapping it with another slide in a 25 x 20 mm area, and press with a weight of 350 g. Cure the sample at 200 °C for 10 minutes. Prepare 12 samples per formulation. Load each end of the sample into a tensile jig (ADMET eXpert 2611) equipped with a 500 N load cell. Apply force to the sample at a controlled rate (0.3 mm / min) until it breaks and record the maximum force used for comparison between samples.

[0273] A schematic diagram of the shear strength test for bonded lap joints is shown below. Figure 5 As shown.

[0274] Adhesive examples, referring to adhesive A (phenolic resin modified with urea, PUF-resol).

[0275] The adhesive is a urea-modified phenolic resin, PUF-resol.

[0276] A phenolic resin was prepared by reacting a 37% aqueous formaldehyde solution (606 g) with phenol (189 g) at a reaction temperature of 84 °C in the presence of a 46% aqueous potassium hydroxide solution (25.5 g) at a rate of approximately 1 °C per minute. The reaction was continued at 84 °C until the resin achieved an acid resistance of 4 and most of the phenol was converted. Urea (241 g) was then added, and the mixture was cooled.

[0277] Acid resistance (AT) indicates the number of times a given volume of adhesive can be diluted with acid without causing the mixture to become cloudy (adhesive precipitation). Sulfuric acid is used to determine the termination criterion in adhesive production; an acid resistance below 4 indicates the end of the adhesive reaction.

[0278] To measure AT, a titrant is prepared by diluting 2.5 ml of concentrated sulfuric acid (>99%) with 1 L of deionized water. Then, 5 mL of the adhesive under study is titrated with this titrant at room temperature while keeping the adhesive in motion by hand-shaking; preferably, a magnetic stirrer and magnetic rod are used. Titration continues until a slight turbidity appears in the adhesive, which does not disappear when the adhesive is shaken.

[0279] Acid resistance (AT) is calculated by dividing the amount of acid (mL) used for titration by the amount of sample (mL):

[0280] AT = (Titration volume used (mL)) / (Sample volume (mL))

[0281] An adhesive was prepared using the obtained urea-modified phenolic resin by adding 25% ammonia (90 mL) and ammonium sulfate (13.2 g), followed by water (1.30 kg).

[0282] The binder solids were then measured as described above, and the mixture was diluted with the required amounts of water and silane for mechanical measurement (15% binder solids solution, 0.5% binder solids in silane).

[0283] Adhesive examples, refer to adhesive B

[0284] The mixture of 75.1% aqueous glucose syrup (19.98 g; therefore effective as 15.0 g glucose syrup), 50% aqueous hypophosphoric acid (0.60 g; therefore effective as 0.30 g, 4.55 mmol hypophosphoric acid) and aminosulfonic acid (0.45 g, 4.63 mmol) in water (30.0 g) was stirred at room temperature until a clear solution was obtained.

[0285] Then add 28% ammonia solution (0.80 g; therefore, effectively 0.22 g, 13.15 mmol ammonia) dropwise until pH = 7.9. Then measure the binder solids (21.2%).

[0286] For mechanical strength studies (15% adhesive solids solution, 0.5% adhesive solids in silane), the adhesive mixture was diluted with water (0.403 g / g adhesive mixture) and 10% aqueous silane solution (0.011 g / g adhesive mixture, Momentive VS-142). The final adhesive mixture used for mechanical strength studies had a pH of 7.9.

[0287] Adhesive Examples, Item 2:

[0288] Add 5.0 g of polyethylene glycol 300 and 1.4 g of Primid XL552 to a mixture of 18.2% unoxidized sulfate lignin aqueous solution (100 g, therefore effectively 18.2 g of lignin) stirred at room temperature. Then measure the binder solids (21.2%).

[0289] For mechanical testing (15% binder solids, 0.5% binder solids in silane), the mixture was diluted with water (0.402 g / g binder mixture) and a 10% aqueous silane solution (0.011 g / g binder mixture, Momentive A1871, pre-hydrolyzed with 10% acetic acid under acetic acid conditions, diluted with water). The final binder mixture for mechanical testing had a pH of 10.2.

[0290] Adhesive composition according to the invention

[0291] In the following text, the entry numbers for the adhesive examples correspond to the entry numbers used in Tables 1-1 to 1-5.

[0292] Adhesive Examples, Item 1:

[0293] 5.0 g of polyethylene glycol 300 and 2.5 g of Primid XL552 were added to a mixture of 18.3% aqueous solution of oxidized sulfate lignin from UPM (100 g, therefore effectively 18.3 g AOL) stirred at room temperature. The binder solids were then measured (21.2%).

[0294] For mechanical testing (15% binder solids, 0.5% binder solids in silane), the mixture was diluted with water (0.402 g / g binder mixture) and a 10% aqueous solution of silane (0.011 g / g binder mixture, Momentive A1871, pre-hydrolyzed with 10% acetic acid under acetic acid conditions, diluted with water). The final binder mixture for mechanical testing had a pH of 10.2.

[0295] Adhesive Examples, Item 7:

[0296] 5.0 g of polyethylene glycol 300 and 5.0 g of Primid XL552 were added to a mixture of 18.3% aqueous solution of oxidized sulfate lignin from UPM (100 g, therefore effectively 18.3 g AOL) stirred at room temperature. The binder solids were then measured (22.6%).

[0297] For mechanical testing (15% binder solids), the mixture was diluted with water (0.496 g / g binder mixture) and a 10% aqueous silane solution (0.011 g / g binder mixture, Momentive A1871, pre-hydrolyzed with 10% acetic acid under acetic acid conditions). The final binder mixture used for mechanical testing had a pH of 10.2.

[0298] Adhesive Examples, Item 10:

[0299] 5.0 g of polyethylene glycol 300 and 3.8 g of Primid XL552 were added to a mixture of 18.3% aqueous solution of oxidized sulfate lignin from UPM (100 g, therefore effectively 18.3 g AOL) stirred at room temperature. The binder solids were then measured (23.1%).

[0300] For mechanical testing, specifically the joint shear test (20% adhesive solids), the mixture was diluted with water (0.155 g / g adhesive mixture). The final adhesive mixture used for mechanical testing had a pH of 10.2.

[0301] Adhesive Examples, Item 14:

[0302] 5.0 g of polyethylene glycol 300 and 30.0 g of Epocros WS700 were added to a mixture of 18.3% aqueous solution of oxidized sulfate lignin from UPM (100 g, therefore effectively 18.3 g AOL) stirred at room temperature. The binder solids were then measured (21.8%).

[0303] For mechanical testing, the cake test (15% binder solids, 0.5% binder solids in silane) was performed by diluting the mixture with water (0.442 g / g binder mixture) and a 10% aqueous solution of silane (0.011 g / g binder mixture, Momentive A1871, pre-hydrolyzed with 10% acetic acid under acetic acid conditions, then diluted with water). The final binder mixture used for mechanical testing had a pH of 10.2.

[0304] Adhesive Examples, Item 26:

[0305] 21.1% based on Green Value SA was stirred at room temperature.

[0306] 5.0 g of polyethylene glycol 300 and 4.4 g of Primid XL552 were added to a mixture of 100 g of an aqueous solution of oxidized alkali lignin (effectively 21.1 g AOL) of Protobind 1000 from Switzerland. The binder solids were then measured (21.1%).

[0307] For mechanical testing, the strip test (15% adhesive solids, 0.5% adhesive solids in silane) was performed by diluting the mixture with water (0.396 g / g adhesive mixture) and 10% aqueous silane solution (0.011 g / g adhesive mixture, MomentiveVS142). The final adhesive mixture used for mechanical testing had a pH of 10.1.

[0308] Examples of oxidized LignoForce:

[0309] Add 5.0 g of polyethylene glycol 300 and 2.5 g of Primid XL552 to a mixture of 18.3% AOL (based on LignoForce from West Fraser, Alberta, US) aqueous solution (100 g, therefore effectively 18.3 g AOL) stirred at room temperature. Then measure the binder solids (21.2%).

[0310] For mechanical testing (15% binder solids, 0.5% binder solids in silane), the mixture was diluted with water (0.402 g / g binder mixture) and a 10% aqueous solution of silane (0.011 g / g binder mixture, Momentive A1871, pre-hydrolyzed with 10% acetic acid under acetic acid conditions, diluted with water). The final binder mixture for mechanical testing had a pH of 10.2.

[0311] The following observations and conclusions can be drawn from Table 1:

[0312] When comparing the difference between the binder component solids content and the binder solids, defined as the binder loss in the examples in Tables 1-1, 1-2, and 1-3, it can be seen that the binder loss in lignin-based binders is similar to or lower than that in references A and B. The applicant believes this is due to the high molecular weight of lignin compared to the lower molecular weight of the reactants in the binder compositions of references A and B. When compared with other binder compositions based on renewable resources (e.g., reference B), using fewer organic raw materials can achieve a higher LOI (loss on ignition) in the final product.

[0313] A comparison of the results in Tables 1-1, 1-2, and 1-3 shows that the oxidation of sulfate lignin is preferred (1 vs. 2) compared to sulfate lignin, the addition of Primid XL552 as a crosslinking agent is preferred (1 vs. 3, 14, and 15) and silane as a coupling agent is preferred (1 vs. 6), resulting in mineral wool products of the present invention with high mechanical strength (aged and unaged), comparable to reference adhesive compositions A and B.

[0314] A comparison of the results in Tables 1-4 shows that the curing temperature affects the final mechanical properties, with the products cured at 220°C exhibiting mechanical properties comparable to reference adhesive compositions A and B.

[0315] A comparison of the results in Tables 1-5 also reveals that the oxidation of alkali lignin has a positive effect on the final mechanical properties—similar to the effect of sulfate lignin oxidation shown in Table 1-1. The effect of curing temperature is also evident here, where increasing the temperature improves mechanical properties, again comparable to reference adhesive compositions A and B.

[0316] Overall, we are able to produce lignin-based, formaldehyde-free adhesive compositions with high renewable material content, lower reaction loss, and mechanical properties comparable to the reference system.

[0317]

[0318]

[0319]

[0320]

[0321]

[0322] The following examples relate to the preparation of oxidized lignin, which can be used as component (i) of the aqueous adhesive composition according to the present invention.

[0323] Example

[0324] Example A - Lignin was oxidized by hydrogen peroxide in an ammonia solution:

[0325] Tables A1.1 and A1.2 provide the amounts of the ingredients used according to Example A.

[0326] In developing the method according to the invention, the inventors first began laboratory-scale experiments, which were conducted on a scale of approximately 1 L.

[0327] Although sulfate lignin is soluble in water at higher pH values, it is known that the viscosity of the solution increases significantly at certain weight percentages. This increase in viscosity is generally attributed to a combination of strong hydrogen bonds and the π-electron interactions of the numerous aromatic rings present in lignin. For sulfate lignin, a sudden increase in viscosity has been observed at approximately 21-22 wt% in water; in this example, 19 wt% sulfate lignin was used.

[0328] In the pH adjustment step, an aqueous ammonia solution is used as the base. Its amount is fixed at 4% by weight based on the total reaction weight. The pH is 10.7 after the pH adjustment step and at the start of oxidation.

[0329] Table A2 shows the CHNS elemental analysis results of sulfate lignin before and after oxidation. Prior to analysis, the samples were heat-treated at 160°C to remove adsorbed ammonia. The analysis indicates that a certain amount of nitrogen became part of the oxidized lignin structure during the oxidation process.

[0330] During the batch experiments, it was determined that adding the full amount of hydrogen peroxide over short time intervals was beneficial for oxidation, contrary to adding peroxide in small amounts over longer periods. In this embodiment, 2.0 wt% H2O2 based on the total reaction weight was used.

[0331] Oxidation is an exothermic reaction, and the addition of peroxides will cause the temperature to rise. In this example, the temperature is maintained at 60°C for three hours during the reaction.

[0332] After oxidation, through 31 The number of lignin functional groups per gram of sample was increased, as determined by P NMR and water titration. 31 Sample preparation for PNMR was performed using 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxophosphazenecyclopentane (TMDP) as the phosphorylation reagent and cholesterol as the internal standard. The NMR spectra of sulfate lignin before and after oxidation are shown below. Figure 4 As shown, the results are summarized in Table A3.

[0333] Figure 6 The images show sulfate lignin and ammonia-oxidized sulfate lignin (AOL). 31 P NMR. The figure shows the different hydroxyl groups and the internal standard, where S, G, and H represent eugenolyl, guaiacolyl, and coumarin (hydroxyphenyl), respectively. The inset shows the signal from the carboxyl group, without shift. Changes in the COOH group were also determined by water titration using the following formula:

[0334]

[0335] Where V 2s and V 1s It is the final volume of the sample, while V 2b and V 1b It is the empty volume. In this case, C acid 0.1M HCl, and m s This represents the weight of the sample. Table A4 shows the values ​​obtained from the water titration method before and after oxidation.

[0336] The average COOH functionality can also be quantified by the saponification value, which represents the number of milligrams of KOH required to saponify 1 gram of lignin. This method can be found in AOCS Official Method Cd 3-25.

[0337] The average molecular weights before and after oxidation were also determined using a PSS PolarSil column (9:1 (v / v) dimethyl sulfoxide / water eluent containing 0.05 M LiBr) and a 280 nm UV detector. The combination of COOH concentration and average molecular weight also allowed for the calculation of the average carboxylic acid group content per lignin macromolecule, and these results are shown in Table A5.

[0338] Example B - Scale-up of lignin oxidation in ammonia using hydrogen peroxide to a pilot-scale operation.

[0339] Hydrogenation of lignin with peroxide is an exothermic process; even on a laboratory scale, the addition of peroxide significantly raises the temperature. This is a natural concern when scaling up chemical processes because the heat generated is related to the cube of the dimension (volume), while cooling typically increases only with the square of the dimension (area). Furthermore, due to the high viscosity of the binder intermediates, process equipment must be carefully selected or designed. Therefore, scale-up is meticulously planned and carried out in several steps.

[0340] The first scale-up step involved using a specialized stainless steel mixer with highly effective mechanical stirring to increase the volume from 1 liter (laboratory scale) to 9 liters. The scale-up only resulted in a slightly higher final temperature than achieved at the laboratory scale, thanks to effective air cooling of the reactor and the slow addition of hydrogen peroxide.

[0341] The next scale-up step was carried out in a closed 200L reactor equipped with a high-efficiency water jacket and a high-efficiency propeller agitator. This time the scale-up was 180L, with hydrogen peroxide added in two steps approximately 30 minutes apart. The scale-up proceeded relatively well, although some foaming was a problem, partly due to the high packing density of the reactor. To control foaming, a small amount of food-grade defoamer was sprayed onto the foam. Crucially, the use of external water cooling allowed for controlled temperature control and a final temperature below 70°C.

[0342] A pilot-scale reaction was conducted in an 800L reactor equipped with a water-cooled jacket and a two-bladed propeller agitator. 158 kg of lignin (UPM LignoBoost™ BioPiva 100) with a dry matter content of 67 wt% was de-agglomerated and suspended in 224 kg of water, and stirred to form a homogeneous suspension. While stirring, 103 kg of 25% ammonia solution was pumped into the reactor, and stirring was continued for another 2 hours to form a dark, viscous lignin solution.

[0343] Over 15 minutes, add 140 kg of 7.5% by weight hydrogen peroxide to the stirred lignin solution at 20-25°C. During and after the addition of hydrogen peroxide, carefully monitor the temperature and foam level, and add cooling water to the cooling jacket to maintain an acceptable foam level and a temperature rise of less than 4°C per minute, with a final temperature below 70°C. After the temperature rise stops, shut off the cooling and re-stir the product mixture for 2 hours before transferring it to a transport container.

[0344] Based on scaled-up operation, it can be concluded that even though the reaction is exothermic, most of the heat of reaction is actually balanced by the heat capacity of water from room temperature to approximately 60°C, with only the last portion needing to be removed by cooling. It should be noted that, for this reason, and due to the short reaction time, this process is ideal for scale-up and process intensification using continuous reactors (e.g., in-line mixers, tubular reactors, or CSTR-type reactors). This will ensure good temperature control and a more defined reaction process.

[0345] Scale-up batch testing showed that the produced oxidized lignin had the same properties as the batches produced in the laboratory.

[0346] Table A 1.1

[0347] The amount of material used in the form in which they are provided:

[0348]

[0349] Table A 1.2

[0350] Dosage of active ingredient:

[0351]

[0352] Table A 2

[0353] Elemental analysis of sulfate lignin before and after oxidation:

[0354]

[0355] Table A 3

[0356] pass 31 Distribution of functional groups in sulfate lignin before and after oxidation obtained by P-NMR:

[0357]

[0358] Table A 4

[0359] COOH group content, expressed in mmol / g, determined by water titration:

[0360]

[0361] Table A 5

[0362] Table A 5. Number-average molar mass (Mn) and weight-average molar mass (Mw), in g / mol, determined by size exclusion chromatography, and the average carboxylic acid group content per lignin macromolecule before and after oxidation.

[0363]

Claims

1. An aqueous adhesive composition for mineral fibers, comprising: - One or more components in the form of oxidized lignin (i); - Component (ii) in the form of one or more cross-linking agents, selected from β-hydroxyalkylamide cross-linking agents and / or oxazoline cross-linking agents; - One or more plasticizers (iii); Based on the dry weight of component (i), component (ii) is present in an amount of 1 to 40% by weight; Based on the dry weight of component (i), component (iii) is present in an amount of 0.5 to 50% by weight.

2. The aqueous adhesive composition according to claim 1, wherein component (i) is one or more oxidized lignin forms, said lignin being selected from sulfate lignin, alkali lignin, lignin sulfonate lignin, organic solvent lignin, or any mixture thereof.

3. The aqueous adhesive composition according to claim 1, wherein component (i) is in the form of one or more oxidized sulfate lignin.

4. The aqueous adhesive composition according to claim 1, wherein component (i) is in the form of one or more alkali-oxidized lignins.

5. The aqueous adhesive composition according to claim 1, wherein component (i) is one or more forms of ammoniated lignin.

6. The aqueous adhesive composition according to claim 1, wherein the content of carboxylic acid groups in component (i) is from 0.05 to 10 mmol / g based on the dry weight of component (i).

7. The aqueous adhesive composition according to claim 1, wherein the content of carboxylic acid groups in component (i) is 0.1 to 5 mmol / g based on the dry weight of component (i).

8. The aqueous adhesive composition according to claim 1, wherein the content of carboxylic acid groups in component (i) is from 0.20 to 1.5 mmol / g based on the dry weight of component (i).

9. The aqueous adhesive composition according to claim 1, wherein the content of carboxylic acid groups in component (i) is from 0.40 to 1.2 mmol / g based on the dry weight of component (i).

10. The aqueous adhesive composition according to claim 1, wherein the content of carboxylic acid groups in component (i) is from 0.45 to 1.0 mmol / g based on the dry weight of component (i).

11. The aqueous adhesive composition according to claim 6, wherein the average content of carboxylic acid groups in component (i) is greater than 1.5 groups per macromolecule of component (i).

12. The aqueous adhesive composition according to claim 1, wherein the average content of carboxylic acid groups in component (i) is greater than 2 groups per macromolecule of component (i).

13. The aqueous adhesive composition according to claim 1, wherein the average content of carboxylic acid groups in component (i) is greater than 2.5 groups per macromolecule of component (i).

14. The aqueous adhesive composition according to claim 1, wherein component (ii) comprises, in an amount of 4 to 20% by weight, based on the dry weight of component (i).

15. The aqueous adhesive composition according to claim 1, wherein component (ii) comprises, in an amount of 6 to 12% by weight, based on the dry weight of component (i).

16. The aqueous adhesive composition according to claim 11, wherein component (iii) is in the form of one or more plasticizers selected from polyethylene glycol, polyether, hydrogenated sugar, phthalate or acid, acrylic polymer, polyvinyl alcohol, polyurethane dispersion, ethylene carbonate, propylene carbonate, lactone, lactam or lactide.

17. The aqueous adhesive composition of claim 16, wherein the acid is adipic acid, vanillic acid, lactic acid, or ferulic acid.

18. The aqueous adhesive composition according to claim 1, wherein component (iii) is in the form of one or more plasticizers having a boiling point of 100 to 280°C.

19. The aqueous adhesive composition according to claim 1, wherein component (iii) is in the form of one or more plasticizers having a boiling point of 120 to 260°C.

20. The aqueous adhesive composition according to claim 1, wherein component (iii) is in the form of one or more plasticizers having a boiling point of 140 to 250°C.

21. The aqueous adhesive composition according to claim 16, wherein component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 150 to 50,000 g / mol.

22. The aqueous adhesive composition according to claim 16, wherein component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 150 to 4000 g / mol.

23. The aqueous adhesive composition according to claim 16, wherein component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 150 to 1000 g / mol.

24. The aqueous adhesive composition according to claim 16, wherein component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 150 to 500 g / mol.

25. The aqueous adhesive composition according to claim 16, wherein component (iii) is in the form of one or more polyethylene glycols having an average molecular weight of 200 to 400 g / mol.

26. The aqueous adhesive composition according to claim 1, wherein component (iii) is present in an amount of 2.5 to 25% by weight based on the dry weight of component (i).

27. The aqueous adhesive composition according to claim 1, wherein component (iii) is present in an amount of 3 to 15% by weight based on the dry weight of component (i).

28. The aqueous adhesive composition of claim 1, wherein it comprises other components in the form of one or more coupling agents (iv).

29. The aqueous adhesive composition of claim 28, wherein the coupling agent is an organofunctional silane.

30. The aqueous adhesive composition of claim 1, further comprising one or more components (v) selected from ammonia or its salts, and amines or any salts thereof.

31. The aqueous adhesive composition of claim 1, wherein it comprises other components in the form of urea.

32. The aqueous adhesive composition according to claim 1, comprising other components in the form of urea, present in 5 to 40% by weight, based on the dry weight of component (i).

33. The aqueous adhesive composition according to claim 1, comprising other components in the form of urea, present in 10 to 30% by weight, based on the dry weight of component (i).

34. The aqueous adhesive composition according to claim 1, comprising other components in the form of urea, present in an amount of 15 to 25% by weight, based on the dry weight of component (i).

35. The aqueous adhesive composition according to any one of the preceding claims, comprising: - One or more components in the form of oxidized lignin (i); - Component (ii) in the form of one or more cross-linking agents, selected from β-hydroxyalkylamide cross-linking agents and / or oxazoline cross-linking agents; - One or more plasticizers (iii); - Components in the form of one or more coupling agents (iv); -Optionally one or more components selected from the form of compounds of ammonia or any salt thereof, and amine or any salt thereof; - Components optionally in the form of urea; -Optional hydrocarbon oil; -Optionally one or more surfactants; -water.

36. The aqueous adhesive composition according to claim 35, wherein the coupling agent is an organofunctional silane.

37. A method for producing a bonded mineral fiber product, comprising the steps of contacting the mineral fibers with an aqueous adhesive composition according to any one of claims 1-15 and curing the aqueous adhesive composition.

38. A mineral fiber product comprising mineral fibers in contact with an adhesive obtained by curing an aqueous adhesive composition according to any one of claims 1-15.

Citation Information

Patent Citations

  • Binder composition, and method for binding fibrous material by using same

    EP3299421A1

  • Mineral fibre sizing composition containing a carboxylic polyacid and a polyamine, preparation method thereof and resulting products

    US20070173588A1

  • Lignin, phenol, and aldehyde condensation process and product

    US3227667A

  • Compound for use as a mineral fibre binder and process for providing such

    US6706853B1

  • Aqueous dispersion of polyester resin, production method of the same, and aqueous coating composition

    US6818699B2